Ocena sprawności specjalnej piłkarzy nożnych Ośrodka Szkolenia Sportowego Młodzieży w Bydgoszczy = Evaluation of the special efficiency foot players The Sports Training Youth in Bydgoszcz - Wesół, Krzysztof; Cieślicka, Mirosława; Zukow, Walery (Journal of Education, Health and Sport, 2016)
Wesół Krzysztof, Cieślicka Mirosława, Zukow Walery. Ocena sprawności specjalnej piłkarzy nożnych Ośrodka Szkolenia Sportowego Młodzieży w Bydgoszczy = Evaluation of the special efficiency foot players The Sports Training Youth in Bydgoszcz. Journal of Education, Health and Sport. 2016;6(12):274-295. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.200192 http://ojs.ukw.edu.pl/index.php/johs/article/view/4058 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.12.2016. Revised 09.12.2016. Accepted: 09.12.2016. Ocena sprawności specjalnej piłkarzy nożnych Ośrodka Szkolenia Sportowego Młodzieży w Bydgoszczy Evaluation of the special efficiency foot players The Sports Training Youth in Bydgoszcz Wesół Krzysztof, Cieślicka Mirosława, Zukow Walery Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Celem głównym tej pracy była ocena sprawności specjalnej w piłce nożnej na podstawie wyników sprawności ogólnej oraz sprawności specjalnej. W badaniach wzięło udział 23 zawodników klasy III gimnazjum, którzy trenują w Ośrodku Szkolenia Sportowego Młodzieży w Bydgoszczy. Wyniki, które uzyskano w badaniach, pozwoliły na wyciągnięcie wielu wniosków, które dotyczyły sprawności ogólnej jak i specjalnej badanej populacji. Głównym wnioskiem z przeprowadzonej analizy jest fakt, że w klasie III gimnazjum, większość piłkarzy nożnych trenujący w Ośrodku Szkolenia Sportowego Młodzieży posiada sprawność specjalną na średnim poziomie. Świadczy o średnia sprawność specjalna wynosi 61 %. Sprawność ogólną na wysokim poziomie posiada w tej klasie 43% badanych, natomiast 57% prezentuje poziom średni. Sprawność ogólna zatem, u zawodników tej klasy, plasuje się na średnim poziomie. Większość zawodników z wyższą liczbą punktów uzyskanych w teście sprawności ogólnej, posiada również wysoką punktację w teście sprawności specjalnej. Świadczy to o tym, że posiadana sprawność ogólna pomaga w sprawności specjalnej. Ewidentnie liczba zdobytych punktów przez poszczególnych zawodników w teście sprawności ogólnej jest wyższa od liczby punktów zdobytych w teście sprawności specjalnej. Zawodnicy z wyższą liczbą punktów z poprzedniego testu, radzą sobie z testem sprawności specjalnej w sposób łatwiejszy i płynniejszy. Zawodnicy z lepszymi wynikami sprawności ogólnej przeważnie zdobywają wyższe rezultaty w sprawności specjalnej oraz wykonują te próby płynniej i sprawniej. Słowa kluczowe: piłka nożna, sprawność specjalna, sprawność ogólna Summary The main aim of this work was to evaluate the efficiency of the special national football team on the basis of the results of the overall performance and efficiency. The studies involved 23 players of class III middle school, who train at the sports training Youth in Bydgoszcz. The results obtained in studies, to draw many conclusions, which were the efficiency of General and special population. The main conclusion of the analysis is the fact that in class III middle school, most of the soccer players who at the sports training of young people has a special performance at medium level. Shows the average efficiency of special is 61%. The overall efficiency at a high level in this class has 43% of those polled, while 57% presents a medium level. Overall efficiency, therefore, players of this class is for intermediate level. Most of the players from the higher number of points obtained in the test overall fitness, it also has a high score in a test of the efficiency of the special. This shows that your overall efficiency helps efficiency. Clearly the number of points earned by the individual players in a test of the efficiency of the total is higher than the number of points scored in a test of the efficiency of the special. Players with a higher number of points from the previous test, deal with the test, the efficiency of the special in a way that is easier and smoother. Riders with better results overall efficiency generally earn higher results in the special performance and carry out these attempts more smoothly and more efficiently. Key words: football, special performance, overall efficiency